Students' Perception of Canva as a Media in Learning English: A Descriptive Study at SMA Negeri 6 Sijunjung - Mey Nanda Nanda; Sitti Fatimah (Universitas Negeri Padang, 2023)
This study aimed to determine how SMA Negeri 6 Sijunjung students felt about using Canva as a teaching tool. This study used a quantitative method to collect data and was a descriptive study with 32 statements on a Likert scale with five scales: 1 (strongly disagree), 2 (disagree), 3 (neutral), 4 (agree), and 5 (strongly agree). The statements were divided into four categories: interest, concern, object, and environment. A total of 19 students from SMA Negeri 6 Sijunjung composed the study's sample. Item validity, namely the product moment, is used in the validity test. Cronbach's alpha was used to test the instrument's reliability, and the reliability value was 0.906. The descriptive method of data analysis was presented as a percentage. The findings showed that students had a positive view of Canva as a tool for learning English. In particular, the positivity of the statements for the sake of interest (7 statements) was above the mean total (4.23%), the positivity of the statements for the sake of concern (8 statements) was above the mean total (4.22%), the positivity of the statements for the object (7 statements) was above the mean (4.16%), and the positivity of the statements for the environment (10 statements) was above the mean (3.90%). As a result, Canva was seen positively by the students at SMA N-6 Sijunjung as a media for learning English.